2022
DOI: 10.1002/oby.23471
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serum and adipose tissue levels of asprosin in patients with severe obesity undergoing sleeve gastrectomy

Abstract: Objective This study aimed to reveal the relationship between obesity and asprosin (fibrillin‐1) in patients undergoing bariatric surgery and to investigate the role of asprosin in obesity etiopathogenesis. Methods The study included 37 patients who underwent laparoscopic sleeve gastrectomy for severe obesity and 37 patients who underwent laparoscopic cholecystectomy for cholelithiasis in the study and control groups, respectively. Blood samples were collected from the patients in the preoperative period to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Asprosin level was considered a potential independent risk factor in obesity etiopathogenesis 37 . Considering ROC analysis results, the present study demonstrated that serum asprosin level compared to serum BDNF had an important predictive and diagnostic value in obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asprosin level was considered a potential independent risk factor in obesity etiopathogenesis 37 . Considering ROC analysis results, the present study demonstrated that serum asprosin level compared to serum BDNF had an important predictive and diagnostic value in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering ROC analysis results, the present study demonstrated that serum asprosin level compared to serum BDNF had an important predictive and diagnostic value in obesity. Cantay et al (2022) found that serum levels of asprosin had an area under the curve (AUC) value of 53.0% and a cutoff value of 6.97 ng/mL, with 51.4% sensitivity and 48.6% specificity 37 . Another study performed the patients with obesity showed that serum levels of asprosin had an AUC value of 77.0% and a cutoff value of 144 ng/mL, with 71% sensitivity and 71% specificity 66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence suggesting an association between asprosin secreted levels and weight loss extent caused by bariatric surgery such as sleeve gastrectomy or cholecystectomy. Two studies reported significant decrease of serum asprosin levels after six months of weight loss surgical intervention ( 41 , 42 ). Concentrations of fasting asprosin were significantly higher in obese individuals than in normal BMI subjects with no significant sex differences ( 41 ).…”
Section: Asprosin Role In Obesity and Obesity-related Disordersmentioning
confidence: 99%
“…Concentrations of fasting asprosin were significantly higher in obese individuals than in normal BMI subjects with no significant sex differences ( 41 ). Notably, obese group was found to express high asprosin levels and immunoreactivity in adipose tissue ( 42 ).…”
Section: Asprosin Role In Obesity and Obesity-related Disordersmentioning
confidence: 99%